The Stuff that Data is Made of. Materialisation Strategies Between the Visible and the Tangible - Manchia, Valentina (E|C, 2023)
Even the most abstract form of visualization can be described as an expressive material structured into a proportionally formed substance. Recently, however, a new paradigm has arisen: data physicalization, i.e., the use of physical artifacts whose geometry or material properties encode abstract data (Y. Jansen et al. 2015; Dragicevic, Jansen, Vande Moere 2021). In parallel, theories of physicalization as well as classification proposals and taxonomic models are emerging. From a semiotic point of view, it seems more relevant to ask how practices and strategies of materialization and rematerialization of data, both in data physicalization and in classical, abstract forms of visualization, contribute to a different narrative and to a greater engagement of the user/observer. The paper deals with this question through the analysis of some examples and projects, including the U-DATInos project by Salvatore Iaconesi and Oriana Persico, which appeal in a particular way to materiality to communicate data and information.